Perceptions and experiences of community-based healthcare professionals in the state of Qatar having do not attempt resuscitation discussions during the COVID-19 pandemic - Audrey Fitzgerald; Conor Fitzgerald; Louise Anderson; Ammar Ali Hussain; Guillaume Alinier; Guillaume Alinier; Guillaume Alinier; Guillaume Alinier (Frontiers in Medicine, 2023)
IntroductionThe values and attitudes of healthcare professionals influence their handling of “do-not-attempt-resuscitation” (DNAR) orders, as does that of the families they interact with. The aim of this study was to describe attitudes, perceptions, and practices among community-based medical practitioners towards discussing cardiopulmonary resuscitation and DNAR orders with patients and their relatives, and to investigate if the COVID-19 pandemic affected their practice in having these discussions.MethodsThis is a researcher-developed online survey-based study which aimed to recruit a convenience sample of respondents from a total population of 106 healthcare professionals working for the Mobile Healthcare Service (MHS), Hamad Medical Corporation Ambulance Service in the State of Qatar.Results33 family physicians, 38 nurses, and 20 paramedics (n = 91) responded to the questionnaire, of who around 40, 8, and 50%, respectively, had engaged in Do Not Attempt Resuscitation discussions during their work with MHS. 15% of physicians who had experience with Do Not Attempt Resuscitation discussions in Qatar felt that the family or patient were not open to having such discussions. 90% of paramedics thought that Do Not Attempt Resuscitation was a taboo topic for their patients in Qatar, and this view was shared by 75% of physicians and 50% of nurses. Per the responses, the COVID-19 pandemic had not affected the likelihood of most of the physicians or nurses (and 50% of the paramedics) identifying patients with whom having a Do Not Attempt Resuscitation discussion would be clinically appropriate.DiscussionOverall, for all three groups, the COVID-19 pandemic did not affect the likelihood of identifying patients with whom a Do Not Attempt Resuscitation discussion would be clinically appropriate. We found that the greatest barriers in having Do Not Attempt Resuscitation discussions were perceived to be the religious or cultural beliefs of the patient and/or their family, along with the factor of feeling the staff member did not know the patient or their family well enough. All three groups said they would be more likely to have a conversation about Do Not Attempt Resuscitation if barriers were addressed.